Performance Evaluation of Distributed Multi Media Wireless Sensor Network - Karamat Khan, Tehmina; Bin Muhammad Yusof, Zulkefli; Shah, Asadullah (International Journal of Engineering and Technology, 2018)
The demand for multimedia services i.e. audio, video and data with improve QoS and optimum utilization of resources in WSNâ€™s has posed new challenges. As the intensity of traffic increases; it demands for higher bandwidth and dedicated resources to reduce packet loss and delay. There have been analytical models proposed where priorities were assigned to video and voice packets to reduce packet loss and optimize resource utilization. In this paper distributed scheme is proposed to handle video, voice and data packets by having multiple sink nodes. There are shared sink nodes where video, voice and data packets are serviced and dedicated sink nodes only for video and voice packets. The proposed scheme has shown that the packet loss for data packets is higher than voice and video packets. The simulation results show that the performance of the network is improved when priorities are assigned to video and voice packets by giving dedicated resources.Â Â